Mortality of Cebus apella by Molineus torulosus Parasitism in Midwestern Brazil - Marina Pacheco Miguel (Acta Scientiae Veterinariae, 2013)
Background: Wild and captivity monkeys are infested by several parasites species, mainly, Strongyloides sp. and Acanthocephala sp, which has been identifi ed as the major causes of illness and death. However, Molineus torulosus is a pathogenic nematode found in Neotropical New World Primates and causes severe illness in small primates due to severe gastrointestinal injury. In South America, the parasite was described in Cebus apella and C. olivecaeus from French Guyana and were verifi ed the occurrence in tropical forests. Thus, it is the fi rst report about M. torulosus infestation in capitivity capuchin monkeys in Brazil. Case: Two capuchin monkeys were presented for necropsy. According to veterinarian the monkeys had about fi ve years old and weighed 0.9 kg and lived in a particular park in urban with 20 to 30 capuchin monkeys group. The veterinarian described that six capuchin monkeys were found dead in two months period. One of the monkeys were found dead and another one had respiratory disturbance, apathy, prostration, cyanotic mucosa, feces with green coloration and death after four days in observation and isolation of the group. Necropsy confi rmed emaciation and moderate splenomegaly, great amount of fi brin on the intestine and presence of multifocal 1 to 2 cm nodules in small intestine with numerous parasites mainly initial portion. In the small intestine, were found several free helminthes in the feces. No parasite was attached in the gut wall. The parasites in the nodules were submitted to a standard nematode key identifi cation, confi rming the infestation by M. torulosus. The parasites were small, slender, pale red, of 4 to 6 mm length. There were no signifi cant macroscopic fi ndings in the other organ systems. The histological examination of nodules sections revealed an intense granulomatous infl ammatory response surrounded by proliferating fi brous connective tissue and the central portion contained a mass of nematode parasites and their eggs surrounded by eosinophilic debris. The small intestine revealed the presence of eggs and larvae at the villi, epithelium and crypts necrosis areas, villi atrophy and congestion, mononuclear infl ammatory reaction. Discussion: There are no reports of Molineus torulosus parasitism in captivity capuchin monkeys in Brazil. The clinical signs described in the present case were unspecifi c and the parasite identifi cation was a necropsy found. However, the infestation with M. torulosus was associated with enteritis and diarrhea. The parasite causes hemorrhagic or ulcerative enteritis, sometimes associated with diverticula of the intestinal wall. Furthermore, the capuchin monkeys death in the present case was assigned with a fi brinous peritonitis and septicemia because a gut wall necrosis caused by M. torulosus infestation. Thus, the high density of M. torulosus in the small intestine is believed to be responsible for the death of these capuchin monkeys. The present report identifi es the nemato